ANALISIS SISTEM PENGENDALIAN INTERN PELAYANAN JASA DAN PIUTANG PADA PT. POS INDONESIA (PERSERO) MALANG - Amelia, Imaniar Rizka; Anita Handayani (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This examination expects to decide inward control framework methodology and decide if interior control has been utilized successfully in help exercises and recording receivables at PT Pos Indonesia (Persero) Malang City. The spot for this evaluation was done at PT Pos Indonesia (Persero) Malang City. The kind of appraisal utilized is plainly dynamic. Internal control uses data reduction techniques, data presentation, and data confirmation as assessment procedures for PT Pos Indonesia (Persero)'s changes in receivables. Whenever seen from the consequences of the survey that has been done, it shows that the pieces of inside control as per COSO's hypothesis in reviewing the degree of precision of approval have been running great since SOP (Standard Work Technique) has been executed, and there is a most elevated credit limit applied by affiliation. Whenever saw according to the viewpoint of isolating commitments between the capacity to record receivables and the capacity to give credit, the ensuing impact of this grouping of consideration additionally shows that inward controls for estimating the degree of recording receivables are adequate to forestall diminishes over of receivables.